2022
DOI: 10.1101/2022.11.09.22282119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Gout with Brain Reserve and Vulnerability to Neurodegenerative Disease

Abstract: Objective To assess the associations between gout, brain structure, and neurodegenerative disease incidence. Methods Using observational and Mendelian randomization analyses we investigated causal relationships between gout and brain health. Exposures included gout diagnosis (from self-report, linked health records and death records) and genetically proxied gout and serum urate. Outcomes were neuroimaging markers of brain structure and neurodegenerative disease incidence (ascertained through self-report, healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Black CN et al found that the severity and duration of symptoms of major depression or anxiety disorders were negatively correlated with uric acid levels [31] .Additionally, it has been reported that gout affects the volume of speci c brain regions as well. In a Mendelian randomization study of gout and brain volume, researchers found that genetically predicted gout was signi cantly associated with gray matter volume in the whole brain, and genetically predicted hyperuricemia was also signi cantly correlated with gray matter volume in several regions, including the cerebellum, midbrain, pons, and brainstem [32] . Compared with this previous study, our study provides a more detailed delineation of brain regions, further revealing the correlation between gout and the more subtle brain regions of the Left Frontal Operculum Cortex and Left Precentral Gyrus.Furthermore,Yang et al, in an imaging study using MRI technology to detect cortical volume in gout patients, found that the cortical thickness in the left upper frontal lobe region of gout patients was thinner than that of the healthy control group [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Black CN et al found that the severity and duration of symptoms of major depression or anxiety disorders were negatively correlated with uric acid levels [31] .Additionally, it has been reported that gout affects the volume of speci c brain regions as well. In a Mendelian randomization study of gout and brain volume, researchers found that genetically predicted gout was signi cantly associated with gray matter volume in the whole brain, and genetically predicted hyperuricemia was also signi cantly correlated with gray matter volume in several regions, including the cerebellum, midbrain, pons, and brainstem [32] . Compared with this previous study, our study provides a more detailed delineation of brain regions, further revealing the correlation between gout and the more subtle brain regions of the Left Frontal Operculum Cortex and Left Precentral Gyrus.Furthermore,Yang et al, in an imaging study using MRI technology to detect cortical volume in gout patients, found that the cortical thickness in the left upper frontal lobe region of gout patients was thinner than that of the healthy control group [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Though direct association between astrocyte and CAD has not been fully elucidated, the underlying mechanisms could be explained by the predominant function of astrocyte in controlling blood glucose and blood pressure 35 , of which the increase are regarded as major risk factors to develop CAD. As for gout, evidence from recent observational studies suggest the association between gout and brain structure 37 , however, the mechanism underlying how brain or which brain cell type affects gout is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[92] Patients with gout have smaller global and regional brain volumes and higher brain iron levels. [93] Elevated serum uric acid, which is involved in iron metabolism, has been increasingly recognized as a risk factor for gout. [94] Iron supplementation exacerbates joint inflammation in mice with acute GA. [95] Targeting iron metabolism to treat GA is also a promising approach.…”
Section: Iron Metabolism and Arthritismentioning
confidence: 99%